Effectiveness of Sexual Counseling on Sexuality of Cancer Patients: A Systematic Review - Nugraha, Rudi; Afiyanti, Yati; Pujasari, Hening; Gayatri, Dewi (Babali Publisher, 2025)
Introduction: Cancer patient care is a complex and ongoing process. The impact of cancer diagnosis and treatment on sexual quality is an important issue in cancer quality of life. Sexual counselling is one of the interventions chosen in handling sexual problems in cancer patients. This review aims to examine the effectiveness of sexual counselling on the sexuality of cancer patients. Methods: Literature searches were conducted through several databases, including PubMed, Scopus, ProQuest, Science Direct, Oxford, ClinicalKey Nursing, EBSCOhost, Springer Link, Taylor & Francis, using predetermined inclusion and exclusion criteria. The selected articles were analyzed based on the intervention method. A total of 15 14,287 articles were extracted and synthesized. Results: 15 intervention articles were obtained showing that sexual counselling effectively affects the sexuality of cancer patients and can be carried out for patients and their partners face-to-face, by telephone, by internet, or via WhatsApp. Conclusion: Sexual counselling programs for cancer patients are effective interventions for sexual problems in cancer patients.